PENERAPAN PERMAINAN â€œPANTUN CERDASâ€ UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS IV-A SDN PADASUKA I PADA MATERI MEMBUAT PANTUN - Wafa, Agung Ali; Djuanda, Dadan; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2017)
Learning to write traditional poetry (pantun) in grade IV-A SDN Padasuka 1 District of North Sumedang, Sumedang City is still low. It showed from the results of students in writing traditional poetry (pantun). Therefore, this study aim is to improve teacher performance, student activities, and student learning outcomes. To settle the problems, the researcher applied a game â€œpantun cerdasâ€ to improve students writing skills. The method that used in this research was classroom action research spiral model by Kemmis and Mc. Taggart which consists of four components: planning, action, observation, and reflection a total ofÂ  three cycles. The results of students who complete the first cycle were 12 students or 43%, in the second cycle increased to 57%, and the third cycle is 25 students or 89% has been completed. Thus, through the application of game â€œpantun cerdasâ€ can improve student learning outcomes in writing traditional poetry (pantun) learning.